Біохімічні показники крові щурів у динаміці опікової хвороби - Бардахівська, К.І.; Гуріна, Н.М.; Ніколаєв, В.Г. (Видавничий дім "Академперіодика" НАН України, 2007)
The burn disease in rats has three main periods which are characterized by changes in the parameters of lipid peroxidation and antioxidant protection, as well as the protein and lipid metabolism. From the first hours after burn injury and till 7–9 days of burn disease in rats, the changes typical of oxidative stress were observed, including the increase in the malonic dialdehyde concentration in blood plasma by 2.5 times and the decrease of the contents of reduced glutathione and natural antioxidants and the catalase activity by 25, 65, and 70%, respectively.